Opportunities and Challenges of Application of Cytosorb Therapy in Sepsis Management - Halim, Mohammad Rabiul; Nishat, Rahatul Jannat (Bangladesh Critical Care Journal, 2024)
Sepsis is a life-threatening organ dysfunction due to a dysregulated host response to infection. In 2017, an estimated 48·9 million incident cases of sepsis were recorded worldwide, and 11·0 million sepsis-related deaths were reported, representing 19·7% of all global deaths.1 Though overall data related to sepsis is poor but it is also a major health care challenge for resource limited countries. Severe sepsis is a significant & common health problem in ICU patients of Bangladesh2. A continuum of severity from sepsis to septic shock and multi-organ dysfunction syndrome (MODS) exists. MODS is a clinical syndrome characterized by the development of progressive and potentially reversible physiologic dysfunction in 2 or more organs or organ systems that is induced by a variety of acute insults, including sepsis. Sepsis leads to malignant intravascular inflammation, coagulopathy, circulatory derangement, tissue hypoxia, cytotoxicity and apoptosis. As a result, dysfunction of vital organ systems occur. Host response and other factors influenc outcome. Patients with sepsis must be treated with-timely, appropriate antibiotics, intravenousfluids, vasopressor and inotropic support & oxygen therapy.3 Other additional treatments including extracorporeal blood purification techniques (BPT). These techniques include hemofiltration, hemoperfusion, intermittent or continuous high-volume hemofiltration (HVHF), plasmapheresis or adsorption.4 The rationale behind such an approach is to achieve “immune homeostasis” which theoretically reduces the potential damage caused by dysregulation of the host response to infection. Given the pivotal role of cytokine production in sepsis, it follows that removal of these substances, through such BPT, may attenuate the response particularly in the early phase of sepsis.5 Indications include 1) Rhabdomyolysis resulting from Reperfusion syndrome, Trauma, Malignant Hyperthermia. 2) External injuries including Sepsis/Septic shock, Hemorrhagic shock, Trauma, Ruptured aortic aneurysm, Post-Cardiac Arrest Syndrome, Cardio-pulmonary resuscitation, Extensive surgery, Organ transplantation, Cardiosurgical intervention, Severe skin and soft tissue damage, Burns, Necrotizing fasciitis, Post-Cardiotomy Syndrome, Acute Respiratory Distress Syndrome. 3) Diseases: Pancreatitis, Liver insufficiency, Renal insufficiency, Stroke, Myocardial infarction, Cardiogenic shock/Heart failure, Tumor Lysis Syndrome, Hemophagocytosis Syndrome. Liver failure/Hyperbilirubinemia bridging to transplant or to recovery, Life-threatening bleeding under Direct Oral Anticoagulants (DOAC)6. Bangladesh Crit Care J September 2024; 12 (2): 79-80